The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s11739-012-0846-1
|View full text |Cite
|
Sign up to set email alerts
|

Multiple systematic reviews: methods for assessing discordances of results

Abstract: AbtractBackground The process of systematically reviewing research evidence is useful for collecting, assessing and summarizing results from multiple studies planned to answer the same clinical question. The term ''systematic'' implies that the process, besides being organized and complete, is transparent and fully reported to allow other independent researchers to replicate the results, and therefore come to the same conclusions. Hundreds of new systematic reviews are indexed every year. The growing number in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 21 publications
(21 reference statements)
0
27
0
Order By: Relevance
“…To summarize the evidence on the effectiveness of HT interventions, we designed a 3-step process [ 30 , 31 ]. First, as a means of evaluating the comparability of the included systematic reviews and the extent to which reviews overlapped in terms of included studies, we carried out a bibliographic analysis that cross-linked individual systematic reviews with cited HT studies ( Multimedia Appendix 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…To summarize the evidence on the effectiveness of HT interventions, we designed a 3-step process [ 30 , 31 ]. First, as a means of evaluating the comparability of the included systematic reviews and the extent to which reviews overlapped in terms of included studies, we carried out a bibliographic analysis that cross-linked individual systematic reviews with cited HT studies ( Multimedia Appendix 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…We have described the rationale, design, and methods in detail in a previous publication [10]. Briefly, the eligibility of studies was assessed, independently, by two reviewers across all phrases in accordance to standard rules and implementing ad hoc forms.…”
Section: Methodsmentioning
confidence: 99%
“…Phase 1. We carried out a systematic search process starting from Clinical Evidence search strategy process, as described elsewhere [10]. Clinical Evidence is the BMJ Group medical textbook synthesizing biomedical evidence on a wide range of globally important clinical conditions [11].…”
Section: Methodsmentioning
confidence: 99%
“…Different scopes of search or different criteria of inclusion and exclusion will result in discordance among the conclusions. (14,15) A review of reviews about stroke rehabilitation therapy was performed to assess the methodological issues of systematic reviews. The methodological flaws of the reviews, in particular non-Cochrane reviews, were identified.…”
Section: Introductionmentioning
confidence: 99%